2014
DOI: 10.1016/j.biopsych.2013.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Impaired Cognitive Control over Working Memory in Schizophrenia

Abstract: Background One of the most common deficits in patients with schizophrenia (SZ) is in working memory (WM), which has wide-reaching impacts across cognition. However, prior approaches to studying WM in SZ have employed tasks that require multiple cognitive-control processes, making it difficult to determine which specific cognitive and neural processes underlie the WM impairment. Methods We used fMRI to investigate component processes of WM in SZ. Eighteen healthy controls (HCs) and 18 patients with SZ perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 54 publications
3
29
2
Order By: Relevance
“…These results are compatible with the effects reported in studies of verbal WM (Bissett et al 2009; Bunge et al 2001; Eich et al 2014; Jonides et al 1998; Nee and Jonides 2008; Nee et al 2007; Nelson et al 2003; Smith et al 2011; Yi and Friedman 2014; Zhang et al 2003). Moreover, we found that nameability and color moderate these effects on ER performance, such that more accurate performance was observed with HN and colored objects than with LN and gray objects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are compatible with the effects reported in studies of verbal WM (Bissett et al 2009; Bunge et al 2001; Eich et al 2014; Jonides et al 1998; Nee and Jonides 2008; Nee et al 2007; Nelson et al 2003; Smith et al 2011; Yi and Friedman 2014; Zhang et al 2003). Moreover, we found that nameability and color moderate these effects on ER performance, such that more accurate performance was observed with HN and colored objects than with LN and gray objects.…”
Section: Discussionsupporting
confidence: 91%
“…A large body of research has examined the effects and resolution of PI in verbal WM (Bissett et al 2009; Bunge et al 2001; Eich et al 2014; Jonides et al 1998; Nee and Jonides 2008; Nee et al 2007; Nelson et al 2003; Smith et al 2011; Yi and Friedman 2014; Zhang et al 2003). By contrast, studies using non-verbal material are scarce, and it remains unclear whether the effects of PI are domain-general or whether they differ across the visual and verbal domains.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even when the memory load is significantly increased, OCD subjects perform like healthy controls. These results contrast with those from people with schizophrenia, who demonstrate clear deficits on this task (Eich et al, 2014; Smith et al, 2011). Performance on working memory tasks like this one may therefore serve as an objective way to dissociate these two disorders (Abbruzzese, Ferri, & Scarone, 1997; Cavallaro et al, 2003).…”
Section: Discussioncontrasting
confidence: 95%
“…Nee & Jonides (2008b) found that selection failure was greater in Suppress than Ignore in healthy younger adults, and that this difference could not be attributed to the overall difficulty of the tasks. In people with schizophrenia, we previously found that the difference-score was not significantly different for HCs and people with schizophrenia in the Ignore task (32.50 vs. 21.44 ms, respectively); however it was significantly different in the Suppress task (278.36 vs. 178.51 ms, respectively), suggesting breakdowns in cognitive control for information already in working memory in people with schizophrenia (Eich, Nee, Insel, Malapani, & Smith, 2014; Smith et al, 2011). …”
Section: Methodsmentioning
confidence: 83%
“…These cognitive impairments represent a major hurdle for efforts aimed at successfully integrating patients back in to the general population (Demeter et al 2013;Eich et al 2014;Kim et al 2014;Luck et al 2012). We tested the performance of MAM animals in tasks designed to assess attention, including the ability to filter task-irrelevant stimuli, and spatial working memory.…”
Section: Executive Function In Mam Animalsmentioning
confidence: 99%